Public-private partnerships: Some lessons from Portugal - Riu Sousa Monteiro (EIB Papers, 2005)
The Portuguese PPP experience demonstrates the effectiveness of PPPs in rapidly developing infrastructure and in improving the quality of public services. But the ultimate goal is economic efficiency, not just effectiveness. On this count, Portugal's PPPs may not have scored as high as they could have. To some extent, this has been inevitable, given that no well-tested blueprint to follow was available when Portugal embarked on the PPP route a decade ago. That said, recent changes to Portugal's institutional framework for PPPs - especially a more rigorous appraisal of PPPs, their long-term budgetary implications, and of the contractual arrangements supporting them - aim at ensuring efficiency in the provision of infrastructure services and, thus, value for money.
Keywords: 330; Public-Private Partnership; Portugal